2015
DOI: 10.1016/j.athoracsur.2015.05.095
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolic Complications of Lung Transplantation: A Contemporary Single-Institution Review

Abstract: The incidence of DVT and PE in lung transplant recipients is high. Posttransplant surveillance and treatment based on findings are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 12 publications
5
46
0
Order By: Relevance
“…The 15% incidence of VTE in our cohort is similar to that reported for LT recipients in the literature, namely 8–29% . The single case of atrial thrombosis in 333 LT patients we recorded is within the expected range; we interpreted this problem as being directly related to the surgical procedure.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The 15% incidence of VTE in our cohort is similar to that reported for LT recipients in the literature, namely 8–29% . The single case of atrial thrombosis in 333 LT patients we recorded is within the expected range; we interpreted this problem as being directly related to the surgical procedure.…”
Section: Discussionsupporting
confidence: 88%
“…Our results show that VTE is a relevant complication following LT, mainly in the early postoperative period and that 90-day extended prophylaxis seems unable to prevent it. The 15% incidence of VTE in our cohort is similar to that reported for LT recipients in the literature, namely 8-29% [8][9][10][11]13,25,26]. The single case of atrial thrombosis in 333 LT patients we recorded is within the expected range; we interpreted this problem as being directly related to the surgical procedure.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Lung transplantation is frequently complicated by VTE with a reported incidence of 8%‐45% . There are a number of traditional risk factors responsible for the increased incidence of VTE post‐transplantation including stasis, indwelling catheters, and a postoperative state.…”
Section: Resultsmentioning
confidence: 99%
“…As early as 1995, Kroshus and colleagues 4 in Dr Bolman's group in Minnesota published, in this very Journal, their concerns about this problem after lung and heart-lung transplantations. Other investigators have also subsequently reviewed the incidence and complications of venous thromboembolic events in the lung transplant population [5][6][7] and suggested that routine screening or surveillance is warranted. However, none of them has actually published a study that officially implemented a routine DVT screening protocol.…”
mentioning
confidence: 99%